Dewan Pertimbangan Presiden Dalam Struktur Ketatanegaraan Indonesia - Prasetya, Brilliant Bintang; Wasti, Ryan Muthiara (Jurnal Hukum & Pembangunan, 2022)
The existence of the Presidential Advisory Council is inseparable from the history of state administration with the political phenomenon of law. Various ideas of pros and cons questioned the position and authority of the country's advisory institutions. The institution which at the beginning of its formation was named the Supreme Advisory Council then turned into a Presidential Advisory Council under the executive rule after the amendment to the 1945 Constitution. The shift raises the peculiarities of the position of advisors not under the authority given by advice. Reflecting on the discourse, this paper reviews how the position and extent of the authority of the Presidential Advisory Council in offsetting the branches of power by exploring the historical, juridical aspects and the study of comparison of similar institutions in various countries of the world. Based on the review, the author is of the view that the Presidential Advisory Council should be separated from the executive power branch and is at the same degree. In addition, there is a need for the authority of legislative advisors that can prevent the supremacy of legislatively monopolizing the formation of legislation. At the end, even though the government does not bind itself to the opinion of advisors, but to maintain the authority of the institution it is necessary to be given the authority of the delivery of motion in state hearing.